Wellness in medical education: definition and five domains for wellness among medical learners during the COVID-19 pandemic and beyond - Cherak, Stephana J. (Med Educ Online, 2021)
Problem: The novel coronavirus SARS-CoV-2 disease (COVID-19) impacted medical learner well-being and serves as a unique opportunity to understand medical learner wellness. The authors designed a formal needs assessment to assess medical learners’ perspectives regarding distress related to disrupted training environments. This Rapid Communication describes findings from a qualitative study which defined medical learner wellness and validated five wellness domains. Approach: We conducted follow-up telephone interviews to an online needs assessment survey to identify a learner definition for wellness and to validate five wellness domains, including social, mental, physical, intellectual, and occupational wellness. Using purposive and maximal variation sampling, 27 students were interviewed from July–August 2020. Thematic analysis was performed using a deductive thematic approach to qualitative analysis. Outcomes: Medical learners defined wellness as a general [holistic] sense of personal well-being – the opportunity to be and to do what they most need and value. Learners validated all five wellness domains for medical education. Learners acknowledged the need for an adoptable and adaptable holistic framework for wellness in medical education. Next steps: We recommend academic medical institutions consider learner wellness a key component of medical education to cultivate learners as a competent collective of self-reliant, scholarly experts. We encourage evaluation of wellness domains in diverse medical learner populations to identify feasible interventions potentially associated with improvements in medical learner wellness.